Data privacy across borders : crafting corporate strategies - Hogenhout, Lambert; Wang, Amanda (Sedona : Technics Publications, 2023)
"Apply a step-by-step approach to develop your organization's global data privacy strategy. Data is everywhere. Organizations continuously use data in new ways, often generating cross-border data flows. At the same time, concern about the use of personal data is growing. Every year, more countries adopt data privacy laws and our expectations increase on how companies respect our private data. A data privacy strategy is no longer just about compliance-it is good business. A clear and effective data privacy program can build customer trust and strengthen a brand's reputation. We cover the art of crafting an effective data privacy strategy that aligns with business objectives and brand positioning yet ensures compliance with relevant laws. Gain a foundational understanding of data privacy issues as a prerequisite to developing a custom strategy. Use our review of the major legislations around the world to guide you in creating a data privacy strategy. Benefit from our insights on the relation between data privacy programs and a data strategy, an IT strategy, and risk management frameworks. Be able to apply methodologies to help you stay on track, such as Privacy by Design and data minimization. Incorporate the cultural and ethical considerations of data privacy across different countries where you may operate. Know how emerging privacy enhancing technologies (PETs) can be powerful tools in implementing your strategy, and pinpoint the intersection between data privacy and AI. The stakes for data privacy have never been higher and this book will help you up your game"--